Implementasi Supervisi Akademik Kepala Madrasah dalam Meningkatkan Profesionalitas Guru di Pondok Pesantren Subulussalam (International Forum of Researchers and Lecturers, 2025)
The head of the madrasah as the leader of the madrasah has a very difficult task in order to improve the quality of the madrasah. Teachers as an important component in education, especially in terms of overcoming various problems related to improving the quality of education, are required to become professional teachers. Minister of National Education Regulation no. 12 of 2007 states that one of the competencies of madrasah heads is that they must have good supervision competencies.